Subjective Well Being Guru Honorer di Pondok Pesantren Darul Falah Lubuk Tarok Kabupaten Sijunjung - Yatri Marnelli; Rini Rahman (AS-SABIQUN, 2022)
The purpose of this study was to describe the subjective well-being of honorary teachers at the Darul Falah Islamic Boarding School, Lubuk Tarok, Sijunjung Regency, and to determine the factors that influence the subjective well-being of the honorary teachers at the Darul Falah Islamic Boarding School, Lubuk Tarok, Sijunjung Regency. The method that researchers use in this study is a qualitative method with a phenomenological approach. The informants who became the source of data in this study were honorary teachers at the Darul Falah Islamic Boarding School, Lubuk Tarok, and Sijunjung Regency. They were selected using a purposive sampling technique. 24 honorary teachers teach at the Darul Falah Islamic Boarding School. However, the informants in this study were based on the criteria that the researchers had determined, namely honorary teachers who taught in the field of Islamic religious education, namely fiqh, Arabic, nahwu, imla’, and monotheism with a teaching period of more than five years. Data collection techniques in this study used three ways: observation, interviews, and documentation. Based on the research that has been done, the subjective well-being of honorary teachers at Darul Falah Islamic Boarding School leads to positive cognitive and affective aspects.